Oxadiazole Derivatives as Dual Orexin Receptor Antagonists: Synthesis, Structure–Activity Relationships, and Sleep‐Promoting Properties in Rats. (5th June 2019) - Brotschi, Christine; Roch, Catherine; Gatfield, John; Treiber, Alexander; Williams, Jodi T.; Sifferlen, Thierry; Heidmann, Bibia; Jenck, Francois; Bolli, Martin H.; Boss, Christoph
Abstract: The orexin system plays an important role in the regulation of wakefulness. Suvorexant, a dual orexin receptor antagonist (DORA) is approved for the treatment of primary insomnia. Herein, we outline our optimization efforts toward a novel DORA. We started our investigation with rac ‐[3‐(5‐chloro‐benzooxazol‐2‐ylamino)piperidin‐1‐yl]‐(5‐methyl‐2‐[1, 2, 3]triazol‐2‐ylphenyl)methanone (3 ), a structural hybrid of suvorexant and a piperidine‐containing DORA. During the optimization, we resolved liabilities such as chemical instability, CYP3A4 inhibition, and low brain penetration potential. Furthermore, structural modification of the piperidine scaffold was essential to improve potency at the orexin 2 receptor. This work led to the identification of (5‐methoxy‐4‐methyl‐2‐[1, 2, 3]triazol‐2‐ylphenyl)‐{( S )‐2‐[5‐(2‐trifluoromethoxyphenyl)‐[1, 2, 4]oxadiazol‐3‐yl]pyrrolidin‐1‐yl}methanone (51 ), a potent, brain‐penetrating DORA with in vivo efficacy similar to that of suvorexant in rats. Abstract : DORA explorers : The orexin system plays an important role in the regulation of wakefulness. Herein, we outline our optimization efforts toward a novel dual orexin receptor antagonist (DORA). Our starting point was compound3, a hybrid of Merck's suvorexant and another published DORA containing piperidine as a core structure. Our work led to the identification of compound51, a potent, brain‐penetrating DORA with in vivo efficacy similar to that of suvorexant in rats.